Driving Factors (Motives) Of Community Aspirations in the Formation of Sub-Districts in Natuna Regency (Case Study of the Formation of Pulau Panjang Sub-District) - Roman Jovanda (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This article presents a comprehensive evaluation of the motives behind community aspirations in the process of forming sub-district in Natuna Regency, with a specific case study focusing on the creation of Sub-districts Pulau Panjang. The study aims to shed light on the crucial role of community aspirations in the sub-district formation process and its implications for local development, welfare, and public representation. Utilizing qualitative research methods, including interviews and document analysis, the study delves into the multifaceted factors influencing community aspirations during the formation of Sub-district Pulau Panjang. It examines the dynamics between the elite and the masses, exploring how the aspirations of the community are considered and accommodated in decision-making processes. Moreover, the research analyzes the challenges faced by the community in articulating their needs and the responsiveness of the governing authorities towards community aspirations. The findings of this study underscore the significance of community aspirations in shaping local governance and development planning. Community aspirations play a pivotal role in ensuring inclusive and responsive sub-district formation, which leads to more equitable distribution of resources and services, fostering social cohesion, and enhancing the overall well-being of the population. Based on the analysis, the article proposes actionable recommendations for policymakers and stakeholders to strengthen community engagement, encourage participatory decision-making processes, and prioritize the incorporation of community aspirations in the formulation of Sub-District Pulau Panjang. By embracing these suggestions, Natuna Regency can foster more inclusive and sustainable local development, empower its citizens, and create a governance framework that truly represents the interests and aspirations of the community. Ultimately, this research aims to contribute to the enhancement of local governance practices and empower communities in their pursuit of a more prosperous and harmonious society.